ASSESSING GENDER EQUALITY IN NEWCASTLE LOCAL MUNICIPALITY, SOUTH AFRICA - Jansen, Debbie; Vyas-Doorgapersad, Shikha (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The study examines the factors influencing the effective implementation of gender equality in the Newcastle Local Municipality (NLM). The study, being qualitative in nature, is based on a single case study considering the NLM as a locus. Information is gathered through literature review. The data is analysed through conceptual analysis. The findings obtained indicate a gender disparity at the NLM in terms of councillor and management positions. There are also social, economic, political, ideological, and institutional factors hampering the achievement of gender equality and, these are comprehensively addressed in the study. The study offers recommendations which can be applied in NLM and other municipalities to enhance gender equality. The importance of involving local government and municipalities in the fight against gender inequality cannot be underestimated. It is therefore necessary to address the existing research gap concerning gender equality in local government.